2015
DOI: 10.3934/publichealth.2015.4.746
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Error Associated with Alternative GIS-based Techniques to Measure Access to Health Care Services

Abstract: The aim of this study was to quantify the error associated with different accessibility methods commonly used by public health researchers. Network distances were calculated from each household to the nearest GP our study area in the UK. Household level network distances were assigned as the gold standard and compared to alternate widely used accessibility methods. Four spatial aggregation units, two centroid types and two distance calculation methods represent commonly used accessibility calculation methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…In public health there is a direct link between the distance patients travel to access health and the reduction of ill health and suffering in a country [ 3 ]. Patients tend to use health facilities more if they are located close to them than if they are far way [ 4 ]. The issue of distance of the patients to the centers is seen as one of the main determinants of use of health services [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In public health there is a direct link between the distance patients travel to access health and the reduction of ill health and suffering in a country [ 3 ]. Patients tend to use health facilities more if they are located close to them than if they are far way [ 4 ]. The issue of distance of the patients to the centers is seen as one of the main determinants of use of health services [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several advanced methodological approaches are used to estimate health accessibility, such as gravity, kernel density, and catchment area models [ 9 ]. However, the conventional and most common techniques used to calculate accessibility in public health research are still the Euclidean and network distance [ 4 ]. Euclidean distance techniques describe a location’s relationship to a source or a set of sources based on the straight-line distance [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental theoretical and methodological differences, which underpin the nonnetwork and non-spatial methods are significant and their effects have been clearly demonstrated in other work. Research has shown that omission of network routes can result in falsely assigning places as accessible (Apparicio and Seguin 2006;Higgs et al, 2012;Mizen et al, 2015). The topography of an area, and the barriers to access contained within, whether built (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The geographic location and allocation of health centers along the terrain pattern (Morphmetry), road connectivity with inhabitant and conditions and accessibility throughout the year are the key component in the utilization of maternal health care services (Fatih & EGRESI, 2013;Akhtar &Izhar, 2010 andGage &Calixthe, 2006). Patients tend to use health facilities more if they are located closer to them than they are far away (Mizen, 2015). Low availability and accessibility of health centers and lack of road connectivity has stimulated the chance of home delivery which consequence increases of infant death.…”
Section: Introductionmentioning
confidence: 99%